Application of Mixed Reality Technology in Vocational Education: A Bibliometric Analysis - Wang Li; Tianyu Zhang; Na Li; Stuart Thomason; Xiaojun Zhang (Tecno Scientifica Publisher, 2026)
Mixed reality (MR) technology, which integrates virtual reality (VR) and augmented reality (AR), has emerged as a transformative tool in vocational education by enabling immersive and interactive learning environments. This study aims to analyze the application status, research hotspots, and future development trends of MR technology in vocational education through a bibliometric approach. Data were collected from Scopus and Web of Science databases, resulting in 47 relevant publications after screening. Bibliometric analysis was conducted using Biblioshiny to evaluate publication trends, keyword co-occurrence, influential authors, and collaboration networks. The results indicate a significant increase in research activity following the release of major MR devices such as HoloLens and Vision Pro. Keyword analysis reveals that “mixed reality,” “augmented reality,” and “professional training” are dominant themes, highlighting the strong focus on immersive learning and skill development. MR applications are widely implemented in engineering, medical training, and professional education, providing safe and efficient simulation-based learning environments. Future research directions emphasize the integration of MR with artificial intelligence, personalized learning systems, and cross-platform applications, as well as improvements in usability and accessibility. This study provides valuable insights for researchers, educators, and policymakers to support the effective and sustainable implementation of MR technology in vocational education.